PHILOSOPHICAL AND SOCIO-PHILOSOPHICAL BASE OF HISTORICAL GARDEN TYPES DEVELOPMENT – FROM CONTINENTAL FRENCH FORMAL GARDEN OF THE 17TH CENTURY TO INSULAR ENGLISH LANDSCAPE GARDEN OF THE 18TH CENTURY - Marie Zgarbová (European Scientific Journal, ESJ, 2014)
This paper would like to enrich the common analyses of the historical changes of the garden and landscape space composition with the deeper philosophical and social context of these changes. The very aim of the presented interdisciplinary research is to point out at rather neglected but very important connection of the aesthetics, composition and creation of garden with the dominant way of thinking of a specific era, i.e. with the main philosophy of the period. Specifically, the research focuses on the period of founding and the authentic existence of the two main types of garden space within the history of garden design and landscape architecture of the west civilisation (French formal garden and English landscape garden). This period, the 17th and the 18th century, is also the era of founding and climax of the modern-day philosophy and social philosophy in Europe. The attention is paid both to the mainland of Europe – represented by the modern-day Rationalism that, as it will be shown below, had an impact on the composition of the gardens of French formal type, and England – represented by the modern-day Empiricism that influenced the inclination to less formal, more landscape-friendly composition of the English landscape school. Both of these philosophical schools raised the thoughts of the Enlightenment and especially Empiricism in England anticipated the Romantic era in which the development of English landscape garden culminates.